ANALISIS PERBANDINGAN KINERJA KEUANGAN PT MULTISTRADA ARAH SARANA, Tbk DAN PT GOODYEAR INDONESIA, Tbk YANG TERDAFTAR DI BURSA EFEK INDONESIA DENGAN MENGGUNAKAN METODE DU PONT SYSTEM - Rizki Fadilla Nasution; Jubi Jubi; Ady Inrawan; Astuti Astuti (JURNAL AKUNTANSI FINANCEIAL STIE SULTAN AGUNG, 2019)
The purpose of this research are : 1. to find out the financial performance of PT Multistrada Arah Sarana, Tbk and PT Goodyear Indonesia, Tbk listed on the Indonesia Stock Exchange using the Du Pont System Method. 2. to find out what factors cause differences in the financial performance of PT PT Multistrada Arah Sarana, Tbk and PT Goodyear Indonesia, Tbk listed on the Indonesia Stock Exchange using the Du Pont System Method.  The author's research was conducted using qualitative descriptive analysis techniques, comparative analysis techniques and inductive analysis techniques.This result of this research be conclused as 1. The financial performance of PT Multistrada Arah Sarana, Tbk is said to be unfavorable because of the company’s ability to profit from sales, assets and equity decreases. 3. Factors that cause the differences between the two companies are the high cost of goods sold and the cost that cause losses to the company, accumulated invenory that reduces sales and company profits, the high total assets of total equity and increased share capital and additional capital causes companies to be unable restore equity.The results of the analysis suggest that both companies are expected to further increase sales and reduce costs that are detrimental to the company in order to be able to increase profits. Keywords: Analysis of Du Pont Sytem, Net Profit Margin, Asset Turnover, Return On Asset, EquityMultiplier, Return On Equity and Financial Performance.